1976
DOI: 10.1210/jcem-43-6-1203
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Circulating Thyroxine, Triiodothyronine and Reverse Triiodothyronine After Radiographic Contrast Agents

Abstract: Thyroid function was studied for 42 days in 58 patients, 28 of whome had euthyroid goiter, after urography (diatrizoic acid), cholangiography (ioglycamic acid), and cholecystography (Naiopanoate). After urography and cholangiography short-lived increases of the serum thyroxine occurred in a few patients, but the mean thyroxine and triiodothyronine concentration did not change. By contrast, 7 days after oral cholecystography serum thyroxine had risen consistently by 22% with a concomittant rise of the free thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
48
0
3

Year Published

1979
1979
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(58 citation statements)
references
References 16 publications
7
48
0
3
Order By: Relevance
“…T4 was also administered to dams in order to increase the rT3 concentration in AF and to emphasize its fall. In this study, the administration of IOP in vivo caused a rise in serum concentrations of T4 and rT3 and a fall in serum concentration of T3 in rats, as previously described in humans and rats [23][24][25][26]. It is known that, in such peripheral tissues as the liver and kidney, T4 is deiodinated to T3, and rT3 is deiodinated to 3,3'-T2 by type I 5'-deiodinase [27].…”
Section: Discussionsupporting
confidence: 69%
“…T4 was also administered to dams in order to increase the rT3 concentration in AF and to emphasize its fall. In this study, the administration of IOP in vivo caused a rise in serum concentrations of T4 and rT3 and a fall in serum concentration of T3 in rats, as previously described in humans and rats [23][24][25][26]. It is known that, in such peripheral tissues as the liver and kidney, T4 is deiodinated to T3, and rT3 is deiodinated to 3,3'-T2 by type I 5'-deiodinase [27].…”
Section: Discussionsupporting
confidence: 69%
“…The conversion is enzymatic, because it is temperature, pH, and substrate concentration dependent (29)(30)(31)(32)(33). Compounds such as iopanoic acid, propylthiouracil, and rT3 have been demonstrated to be potent inhibitors of T4 to T3 conversion in vitro (29,33,34) and in vivo (35)(36)(37). Visser et al (38) first reported the importance of sulfhydryl groups in the conversion of T4 to T3 because thiol protective agents such as glutathione or dithiothreitol (DTT) added in vitro enhanced 5'-deiodinating enzyme activity, whereas thiol oxidizing agents abolished it.…”
Section: Introductionmentioning
confidence: 99%
“…propylthiouracil (23,24), glucocorticoids in high doses (25)(26)(27), certain radiographic contrast media (28,29), and the beta adrenergic blocking agents, propranolol (30) and amiodarone (31). It has generally been assumed that all of these factors act primarily to decrease production of T3 from T4, rather than to increase peripheral degradation ofT3, and direct studies have shown this to be true in the case of cirrhosis (5,22), fasting (12,32), and diabetes (15).…”
mentioning
confidence: 99%